A saturated vapor pressure explicit model with temperature and ion concentration for multi-component liquid desiccants. (5th February 2023) - Che, Chunwen; Yin, Yonggao; Mao, Hongcai
Graphical abstract: Highlights: A saturated vapor pressure explicit model with temperature and ion concentration. Prediction of the saturated vapor pressure of multi-component liquid desiccants. The model has a simpler framework and significant computational reduction. Applicable for the calculation of conventional salt and ionic liquid solutions. Potential for direct extension and reduced dependence on experimental data. Abstract: A saturated vapor pressure model with a wide range of applications (covering traditional salt solutions and emerging ionic liquid solutions) and simple frame form is the foundation of the research in the field of solution gas–liquid equilibrium. The existing typical thermodynamic models usually improve the prediction accuracy at the cost of complex forms (such as increasing the number of adjustable parameters), resulting in highly nonlinear functions, which are not convenient for practical calculation. Based on the theory of statistical thermodynamics and considering the dipole interaction of ion-water molecules, this paper proposes a saturated vapor pressure explicit model with temperature and ion concentration for salt and ionic liquid multi-component liquid desiccant, in which only three adjustable parameters are introduced to characterize each ion. Compared with the experimental data and several typical thermodynamic models, the results show that the prediction accuracy of the model is comparable to those of typical models. However, its advantage over these typical models is its simpler framework and significant computational reduction. Through the application of some examples, it is found that the new model can have the potential of direct extension, which is manifested: from one temperature range to another temperature range, from ions to compounds, from single-component to multi-component, and from the water system to other solvent systems. This demonstrates that the three adjustable parameters introduced for ions in the model have clear physical meanings, which can significantly reduce the dependence on experimental data. The proposed model can quickly calculate the saturated vapor pressure of the solution containing inorganic salts, organic acid salts, and ionic liquids, and can guide the optimization of dehumidifying materials.